A comparative study of arachnid communities in rehabilitated bauxite mines - Mawson, P. (1986)
A study was made of arachnid (araneid, opilionid, and scorpionid) communities in rehabilitated bauxite mines operated by Alcoa of Australia Ltd.,and in surrounding jarrah (Eucalyptus marginata) forest at Jarrahdale,45km south-east of Perth,Western Australia. Pitfall trapping,litter sampling, and unit-area visual searches were used to sample the arachnid populations of three rehabilitated bauxite minesites and two natural jarrah forest sites , each with differing histories. Measurement of species diversity and richness within the populations indicate that atleast 8 years is required for the habitats within a rehabilitated bauxite minesite to reach a level of development where they are capable of supporting an arachnid community comparable with that of the surrounding undisturbed jarrah forest. Habitat features such as leaf litter depth, percentage ground cover,and the number of trees taller than 1.5m were found to have a significant influence on the number of species and individuals in the community. Suggestions are made as to how more rapid development of complex communities in the rehabilitating bauxite minesites can be achieved.